The Potential of a Laser-Aspiration Solution for Refractive Lens Exchange - D. E. Arakelyan; S. Yu. Kopaev; I. A. Il’inskaya; V. V. Pominova (Oftalʹmologiâ)
Introduction. This review presents the current knowledge about the methods of lens surgery for the correction of refractive errors in patients with presbyopia and other refractive errors. And also about possible methods of minimization of ultrasound load during the surgery.Purpose. To present current relevant literature scientific knowledge on refractive lens surgery, possible ways of minimization of ultrasound load and new IOL models.Material and methods. To perform the review the literature references were searched through the abstract databases PubMed and Scopus for the period up to and including 2023 using the keywords “zero phaco”, “refractive lens exchange”, “presbyopia”, “femtosecond laser”, “U/S phaco”, “premium IOL”, “refractive error surgery”, “endothelial dystrophy”. A total of 76 articles related to the review topic were selected.Results. Multiple studies confirmed efficacy, safety and fast visual rehabilitation after lens surgery with maximal ultrasound load reduction, in particular in patients with metabolic disorders and predisposition to corneal dystrophies.Conclusion. The literature review suggests that with increasing patient expectations and the use of premium IOLs in the era of refractive lens surgery, predictability and accuracy have become essential. Thus, the technology of safe lens femtosurgery has greatly improved surgical techniques and has revolutionized ophthalmic surgery in recent decades.